Natural Protein Intake in Children with Phenylketonuria - Pinto, Alex (2023)
Funding Information: A.P. received an educational grant from Cambrooke Therapeutics and grants from Vitaflo International, Nutricia, Merck Serono, Biomarin, Mevalia, Galen, and Applied Pharma Research to attend scientific meetings. This project is also part of A.P’s PhD, which is funded by Vitaflo International. A.D. received research funding from Vitaflo International and financial support from Nutricia, Mevalia, and Vitaflo International to attend study days and conferences. J.C.R. was a member of the European Nutritionist ExpertPanel (Biomarin), the Advisory Board for Applied Pharma Research, Vitaflo, Synlogic, Biomarin, and Nutricia, and received honoraria as a speaker from APR, Merck Serono, Biomarin, Nutricia, Vitaflo, Cambrooke, PIAM, and Lifediet. S.E. received research funding from Nutricia and financial support from both Nutricia and Vitaflo International to attend study days and conferences. C.A. received honoraria from Nutricia and Vitaflo International to attend study days and conferences. A.M. has received research funding and honoraria from Nutricia, Vitaflo International, and Biomarin. She is a Member of the Advisory Board Element (Danone-Nutricia). ® Publisher Copyright: © 2023 by the authors.